Glycemic effects of vildagliptin in patients with type 2 diabetes before, during and after the period of fasting in Ramadan. (February 2014) - Malha, Line P.; Taan, Ghazi; Zantout, Mira S.; Azar, Sami T.
Objective: To study the incidence of hypoglycemia, glycemic control and body weight changes in patients with type 2 diabetes treated with vildagliptin and metformin versus another group treated with sulphonylureas and metformin during and after the period of fasting in Ramadan. Patients and methods: This is a randomized open-label clinical trial that recruited 69 patients previously treated with a combination therapy of metformin and sulphonylurea. Patients in the control group were maintained on their usual metformin and sulphonylurea regimen with dose adjustment for the fasting period. Patients in the study group were given vildagliptin 50 mg twice daily (at Suhur and at Iftar). One group remained on the previous background therapy unchanged and the other group was switched from sulphonylurea to vildagliptin in combination with metformin. Four visits were scheduled, one before the beginning of Ramadan (baseline), a second visit at mid Ramadan, a third at the end of Ramadan and a final visit 1 month after the end of Ramadan. At every visit, patients were assessed for hypoglycemic events and patient education was given on lifestyle needs and hypoglycemia monitoring and management. Results: The calculated change in hemoglobin A1c from baseline to last visit was similar for both groups. The incidence of hypoglycemia during Ramadan was higher in the control group (26 episodes versus 19 episodes in the study group); this result was not statistically significant ( p = 0.334). However, the number of patients who dropped out from the study because of discomfort due to treatment and fear of hypoglycemia was higher in the control group. Conclusion: For patients who insist on observing the fast, physicians can allow it only with close follow up and monitoring for hypoglycemic events, and vildagliptin may be a better agent than sulphonylurea.